Fabrication Techniques for Ocular Prostheses – An Overview. (20th February 2014) - Goiato, Marcelo Coelho; Bannwart, Lisiane Cristina; Haddad, Marcela Filié; dos Santos, Daniela Micheline; Pesqueira, Aldiéris Alves; Miyahara, Glauco Issamu
Abstract: The goals of treatment with ocular prostheses are to restore facial aesthetics and self-esteem to anophthalmic patients. Fabricated in acrylic resin, artificial eyes should be aesthetically pleasing, scratch-resistant, and adequately polished. Use of a prosthesis without such characteristics can lead to psychological damage, as well as infection and inflammation due to the accumulation of microorganisms and other substances on an irregularly shaped prosthesis. The present literature review describes the different techniques for fabricating ocular prostheses. Reproduction of the iris color and color stability are important factors that promote adequate aesthetics. The fabrication of an individual ocular prosthesis in acrylic resin provides satisfactory aesthetic results because the impression process establishes the defect contour. Additionally, the iris and sclera can be individually characterized. As the techniques, materials, and manufacturing methods for ocular prostheses continue to evolve, the aesthetics and functionality of prostheses will also improve.